A noise reduction circuit for television - De Leon, Hilary L.
This paper aims to develop a practical device to improve television reception in areas where the signals are weak and perturbed by propagation noise. Some of the general techniques of solving the classical problem of signal detection in noise are reviewed and examined to supplement the search for a solution. Based on the properties of addictive noise in the Television system a non-linear filter is developed with time-variant passband characteristics, altering in a manner which follows the signal's frequency content. A practical filter circuit is initially designed, analyzed, and tested in the laboratory and with actual receivers. Certain modifications are applied based on the results of experiment and theory. The circuit is found capable of noise reduction although resolution suffers in some cases. To improve the filter's performance, further refinements on the work are suggested.